(3TQM efXheI GdOQIs - (3cGTa GdZWGA, YHGS Hf MSf Hf LYaQ, J(B1322(3g`s
(3ChdgG (B:s
(3GdeGA eG Sej eGA eWdbG(B***(3aVdG Ydi GdfGS WghQG NdbGs
(3BNQgG (B:s
(3hUdgeG HCMSf GdUdGI(B***(3ef ML Ch UjGe Ch UdGIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B30s
(3GdPQjYI(B:(3L(B13(3,U(B144(3,Qbe(B862s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis